NMDA Receptor Activity in Neuropsychiatric Disorders - Lakhan, Shaheen E.; Caro, Mario; Hadzimichalis, Norell (Frontiers in Psychiatry, 2013)
N-Methyl-D-aspartate (NMDA) receptors play a variety of physiologic roles and their proper signaling is essential for cellular homeostasis. Any disruption in this pathway, leading to either enhanced or decreased activity, may result in the manifestation of neuropsychiatric pathologies such as schizophrenia, mood disorders, substance induced psychosis, Huntington's disease, Alzheimer's disease, and neuropsychiatric systemic lupus erythematosus. Here, we explore the notion that the overlap in activity of at least one biochemical pathway, the NMDA receptor pathway, may be the link to understanding the overlap in psychotic symptoms between diseases. This review intends to present a broad overview of those neuropsychiatric disorders for which alternations in NMDA receptor activity is prominent thus suggesting that continued direction of pharmaceutical intervention to this pathway may present a viable option for managing symptoms.